Rapid Homogeneous Immunoassay to Quantify Gemcitabine in Plasma for Therapeutic Drug Monitoring. Issue 3 (June 2017) - Kozo, Daniel; Ross, Matt W.; Jarrah, Justin; Barrett, Michael; Harney, Rebecca L.; Courtney, Jodi B.; Baburina, Irina; Holleran, Julianne L.; Beumer, Jan H.; Peters, Godefridus J.; Honeywell, Richard J.; Salamone, Salvatore J.
Abstract : Background: Gemcitabine (2′, 2′-difluoro-2′-deoxycytidine) is a nucleoside analog used as a single agent and in combination regimens for the treatment of a variety of solid tumors. Several studies have shown a relationship between gemcitabine peak plasma concentration (Cmax ) and hematological toxicity. An immunoassay for gemcitabine in plasma was developed and validated to facilitate therapeutic drug monitoring (TDM) by providing an economical, robust method for automated chemistry analyzers. Methods: A monoclonal antibody was coated on nanoparticles to develop a homogenous agglutination inhibition assay. To prevent ex vivo degradation of gemcitabine in blood, tetrahydrouridine was used as a sample stabilizer. Validation was conducted for precision, recovery, cross-reactivity, and linearity on a Beckman Coulter AU480. Verification was performed on an AU5800 in a hospital laboratory. A method comparison was performed with (LC-MS/MS) liquid chromatography tandem mass spectrometry using clinical samples. Selectivity was demonstrated by testing cross-reactivity of the major metabolite, 2′, 2′-difluorodeoxyuridine. Results: Coefficients of variation for repeatability and within-laboratory precision were <8%. The deviation between measured and assigned values was <3%. Linear range was from 0.40 to 33.02 μ/mL (1.5–125.5 μM). Correlation with validated LC-MS/MS methods was R 2 = 0.977. The assay was specific for gemcitabine: there was no cross-reactivity to 2′, 2′-difluorodeoxyuridine, chemotherapeutics, concomitant, or common medications tested. Tetrahydrouridine was packaged in single-use syringes. Gemcitabine stability in whole blood was extended to 8 hours (at room temperature) and in plasma to 8 days (2–8°C). Conclusions: The assay demonstrated the selectivity, test range, precision, and linearity to perform reliable measurements of gemcitabine in plasma. The addition of stabilizer improved the sample handling. Using general clinical chemistry analyzers, gemcitabine could be measured for TDM. Abstract : Supplemental Digital Content is Available in the Text.